In Vitro Assessment of Azole and Amphotericin B Susceptibilities of Malassezia spp. Isolated from Healthy and Lesioned Skin - Chebil, Wissal; Haouas, Najoua; Eskes, Elja; Vandecruys, Paul; Belgacem, Sameh; Belhadj Ali, Hichem; Babba, Hamouda; Van Dijck, Patrick (Journal of fungi (Basel), 2022)
Malassezia yeasts have recently gained medical importance as emerging pathogens associated with a wide range of dermatological and systemic infections. Since standardized methods for in vitro antifungal susceptibility testing have not yet been established for Malassezia spp., related diseases are always treated empirically. As a result, a high rate of recurrence and decreased antifungal susceptibility have appeared. Thus, the aims of the study were to assess and analyze the in vitro susceptibility of Malassezia isolated from pityriasis versicolor (PV) lesions and healthy controls. A total of 58 Malassezia strains isolated from PV patients and healthy controls were tested. In vitro antifungal susceptibility testing was conducted using the CLSI broth microdilution with some modifications. Candida spp. criteria established in accordance with CLSI guidelines were used for data interpretation. Ketoconazole and posaconazole seemed to be the most effective molecules against Malassezia species. However, considerable percentages of itraconazole, fluconazole, and amphotericin B ‘‘resistant’’ strains (27.6%, 29.3%, and 43.1%, respectively) were revealed in this study. Malassezia furfur, M. sympodialis, and M. globosa showed different susceptibility profiles to the drugs tested. These results emphasize the importance of accurately identifying and evaluating the antifungal susceptibility of Malassezia species in order to guide a specific and effective treatment regimen.